2010
DOI: 10.1021/jz101394u
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structure of Ac-Alan-LysH+ Polyalanine Peptides (n = 5,10,15) in Vacuo: Helical or Not?

Abstract: The polyalanine-based peptide series Ac-Alan-LysH + (n=5-20) is a prime example that a secondary structure motif which is well-known from the solution phase (here: helices) can be formed in vacuo. We here revisit this conclusion for n=5,10,15, using density-functional theory (van der Waals corrected generalized gradient approximation), and gas-phase infrared vibrational spectroscopy. For the longer molecules (n=10,15) α-helical models provide good qualitative agreement (theory vs. experiment) already in the ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
146
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(153 citation statements)
references
References 45 publications
7
146
0
Order By: Relevance
“…At 800 K the polypeptide is essentially unfolded after 7 ps and remains unfolded up to 30 ps. It is remarkable that our PBE þ vdW results are thus far consistent with the experimental upper limit for helix stability of T % 725 K, while this is not at all the case for plain PBE results, not even for 3 10 instead of . In addition, also the conformational landscapes with and without vdW interactions differ markedly from one another.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…At 800 K the polypeptide is essentially unfolded after 7 ps and remains unfolded up to 30 ps. It is remarkable that our PBE þ vdW results are thus far consistent with the experimental upper limit for helix stability of T % 725 K, while this is not at all the case for plain PBE results, not even for 3 10 instead of . In addition, also the conformational landscapes with and without vdW interactions differ markedly from one another.…”
supporting
confidence: 73%
“…In fact, in vacuo proteins frequently preserve the secondary structure (helices and sheets) observed in solution, and recent results [7] have shown that even tertiary and quaternary structures can be transferred into the gas phase. Joint experimental and ab initio theoretical studies can now successfully determine the geometries of small gas-phase peptides [8][9][10]. Nevertheless, many fundamental questions remain open, such as: (1) How stable is the folded polypeptide helix in comparison to other (meta)-stable structures?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar fluxional behavior for Si 6 [31,40] lead to a broadening of the IR absorption bands. We have investigated the possibility that dynamic and anharmonic effects are responsible for the band broadening in the IR-MPD spectrum of Si 16 V þ using a molecular dynamics (MD) simulation performed with the FHI-AIMS program [41,42]. An IR spectrum is obtained from the MD trajectory as the Fourier transform of the autocorrelation function of the time-dependent dipole moment [43].…”
Section: Prl 107 173401 (2011) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…1,2,[5][6][7][8][9] For complex molecules, structural assignment by action spectroscopy methods requires comparison with computed spectra. In recent decades, advances in quantum chemistry methods and computer hardware have established density functional theory (DFT) as the framework of choice to compute IR and optical spectra.…”
Section: Introductionmentioning
confidence: 99%